Growth Response and Yield of Red Spinach (Amaranthur tricolor L) Due to Shade Present and Manure - Abdul Wachid; Syaifur Rizal (Nabatia, 2019)
The Aim of this research to determine the growth response and yield of red spinach due to shade present and manure. This research was conducted in Kedungboto, Beji, Pasuruan regency from March until May 2019. The study design was splitplot with the main plot was percentage of shade P0 (without shade), P1 (50% shade), P2 (60% shade), and P3 (70% shade) while subplot was goat manure K1 (25 ton/ha) and K2 (50 ton/ha). The data were then analyzed using Anova and further test LSD 5%. The result was interaction between shade present and goat manure not founded. Shade present has significant effect on plant height, leaf width, and stem diameter at all observations, wet and dry weight of plants, and number of leaves at all observations except 7 DAP. The application of goat manure significant affected on plant height, leaf width, and stem diameter at all observations, number of leaves at 28 and 35 DAP, and the wet and dry weight of red spinach plants.